2014
DOI: 10.1080/13506285.2014.890989
|View full text |Cite
|
Sign up to set email alerts
|

Are summary statistics enough? Evidence for the importance of shape in guiding visual search

Abstract: Peripheral vision outside the focus of attention may rely on summary statistics. We used a gaze-contingent paradigm to directly test this assumption by asking whether search performance differed between targets and statistically-matched visualizations of the same targets. Four-object search displays included one statistically-matched object that was replaced by an unaltered version of the object during the first eye movement. Targets were designated by previews, which were never altered. Two types of statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Freeman and Simoncelli ( 2011 ) demonstrated that a full-field version of this encoding can produce visual metamers for a fixating observer. Alexander et al ( 2014 ) showed that observers performing a search task made different saccades to an array of teddy bears than they made to an array of teddy bear mongrels (synthesized using only local summary statistics). This suggests that peripheral vision has access to additional shape features, either through additional summary statistics or through interactions of multiple overlapping pooling regions.…”
Section: What Makes Search Easy or Hard?mentioning
confidence: 99%
“…Freeman and Simoncelli ( 2011 ) demonstrated that a full-field version of this encoding can produce visual metamers for a fixating observer. Alexander et al ( 2014 ) showed that observers performing a search task made different saccades to an array of teddy bears than they made to an array of teddy bear mongrels (synthesized using only local summary statistics). This suggests that peripheral vision has access to additional shape features, either through additional summary statistics or through interactions of multiple overlapping pooling regions.…”
Section: What Makes Search Easy or Hard?mentioning
confidence: 99%
“…Could such visualizations of summary statistics as yielded by the P-S model be enough to influence semantic scene and possibly even object processing? While the P-S algorithm was originally not developed to study scene understanding, it turns out to be an excellent tool for investigating whether summary statistics are sufficient for influencing semantic scene and possibly even object processing: Naturalistic scenes are not homogenous and therefore the algorithm discards the spatial relations of a scene’s basic visual features and ultimately its global shape 23 , rendering it apparently meaningless 24 , while selectively preserving the basic visual features on the local level.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, participants might have been able to categorize and verbalize the color differences (e.g., search for blue among yellow and orange) but not the shape differences (shape targets were all somewhat cube-ish). Classical computerized search studies typically relied on clearly distinguishable categories for shape searches as well (e.g., search for a diamond among squares), and while there is evidence that shape information can be beneficial for guiding attention in the search [39], this is not undoubted [37] and it could be that shape is only a strong guiding attribute when verbal categories can be established. However, a computerized study investigating attentional dynamics in a color-shape conjunction task found that while color distractors reliably captured attention, while shape distractors did not, although they were defined in a verbalizable category [40].…”
Section: Discussionmentioning
confidence: 99%